G607(P) Teaching effective adolescent consultation in healthcare – for students (TEACHES). (May 2019) - Barnes, F; Wood, D
Abstract : Effective consultation with adolescents and young adults (AYA) is important. When ineffective, results include failure to reach the appropriate diagnosis, reduced compliance and reduced healthcare attendance. 1 Given the rise in health problems experienced by young people, 2 it is vital that prospective doctors are confident in communicating with adolescents. Evidence from randomised controlled trials shows that effective communication with AYA can be taught. 3 Aims: This project aimed to evaluate the effectiveness of adolescent specific teaching delivered to a group of fourth year Child Health medical students at a UK University. Methods: Students were offered an optional two-hour mixed methods educational workshop on effective consultation, including psychosocial assessment using the HEADSSS tool. Key topics covered included raising issues of confidentiality, offering the chance to be seen without parents, identifying passport symptoms and establishing a rapport. Student questionnaires to assess self-reported confidence were completed at the start of placement, immediately following the targeted two-hour workshop and at the end of the eight-week attachment. Results: 42 students in two cohorts on placement between March and August 2017 completed initial questionnaires, with 29 completing the workshop. Results showed a statistically significant increase in self-reported confidence in all areas assessed, and particularly the ability to identify passport symptoms. This universal increase in confidence was maintained at the end of placement, with further gains reported in some areas. There was no data available for students who did not complete the workshop, to assess results without intervention. Free text responses reported that opportunities to practice discussing confidentiality and passport symptoms were particularly valued. A number of students identified a greater understanding of potential barriers to communication as the main benefit. More role-play was requested. The fact that patients were frequently deemed 'unsuitable for students' was identified as the main barrier to practice. Conclusion: Results support the development of AYA communication teaching; with statistically significant increases in student self reported confidence and efficacy seen in all areas. Comparison of change in self-reported confidence of students undertaking the Child Health module where similar workshops are not currently available is being undertaken. References: Silber TJ. Approaching the adolescent patient. Pitfalls and solutions. Journal of adolescent health care: Official publication of the Society for Adolescent Medicine 1986;7(6 Suppl):31S–40S. Ginsburg KR, Slap GB. Unique needs of the teen in the health care setting. Current opinion in pediatrics1996;8(4):333–337. Sanci LA, Ker J, Coffey CMM, Veit FCM, Carr-Gregg M, Patton GC, Day N, Bowes G. Evaluation of the effectiveness of an educational intervention for general practitioners in adolescent health care: randomised controlled trialCommentary: Applying the BMJ's guidelines on educational interventions. Bmj2000;320(7229):224–230.